Twinning mediated plasticity in high entropy CoCr1.3FeNi0.7MnNbx (x = 0.3, 0.367, 0.4) ultrafine lamellar eutectic by tuning stacking fault energy. (1st April 2023) - Potnis, Gaurav; Goswami, Debottam; Das, Jayanta
Abstract: We report the twin mediated plasticity in arc-melted high entropy CoCr1.3 FeNi0.7 MnNb x (0 ≤  x   ≤  0.4) ultrafine lamellar eutectic by tuning stacking fault energy. The phases in eutectic microstructure are identified as FCC phase and HCP-Fe2 Nb-type Laves phase with an average lamellae thickness of 323–482 nm. The stacking fault energy of the FCC phase is 11 mJ/m 2, as estimated through ab initio calculation and x-ray diffraction peak profile analysis. The concurrent effect of dislocation-slip and twinning deformation in low SFE FCC lamellae along with dislocation-nanotwin interaction have been observed under transmission electron microscopy, which resulted in high strain hardening, high strength of 1.2 GPa, and compressive plasticity of ∼17%. The simultaneous occurrence of multiple deformation mechanism under compression in this novel study provides the basis to design high strength and ductile eutectic high entropy alloy by tuning stacking fault energy. Graphical abstract: Image, graphical abstract